A Review of Static and Dynamic Data Replication Mechanisms for Distributed Systems - Bhuvaneswari, R; Ravi, T.N (International Journal of Computer Sciences and Engineering, 2025)
Huge dataset is widely used in various scientific applications. Hence, data replication is highly required to manage large volumes of data in a distributed manner. This improves the data access rate, reduces access latency and increases data availability. This paper presents a comprehensive review of the existing static and dynamic replication mechanisms along with the features. Static mechanisms determine the location of replication nodes during the design phase while the dynamic mechanisms select the replication nodes at the runtime. The dynamic replication approaches allow their associated replication strategies to be adjusted at the runtime according to the changes in user behavior and network topology. Also, they are applicable for a service-oriented environment where the number and location of the users who intend to access data often have to be determined in a highly dynamic fashion.